Prognostic significance of KMT2A-PTD in patients with acute myeloid leukaemia: a systematic review and meta-analysis. Issue 2 (1st February 2023) - Ye, Wu; Ma, Mingzhu; Wu, Xia; Deng, Jili; Liu, Xiaoyan; Zheng, Xue; Gong, Yuping
Abstract : Objectives: Whether KMT2A -PTD has a prognostic impact on patients with acute myeloid leukaemia (AML) is controversial. Therefore, we conducted a meta-analysis to assess the prognostic value of KMT2A -PTD in patients with AML. Methods: Eligibility criteria: we included studies concerning the prognostic value of KMT2A -PTD in patients with AML. Information sources: Eligible studies were identified from PubMed, Embase, Medline, Web of Science, Cochrane Library and Chinese Biomedical Database. The systematic search date was 19 December 2020. Risk of bias: Sensitivity analysis was used to evaluate the stability and reliability of the combined results. Begg's and Egger's tests were used to assess the publication biases of studies. Synthesis of results: We calculated the pooled HRs and their 95% CIs for overall survival (OS) and event-free survival (EFS) by Stata V.12 software. Results: Included studies: 18 studies covering 6499 patients were included. Synthesis of results: KMT2A -PTD conferred shorter OS in total population (HR=1.30, 95% CI 1.09 to 1.51). In the subgroup analysis, KMT2A -PTD also resulted in shorter OS in karyotypically normal AML patients (HR=2.72, 95% CI 1.83 to 3.61) and old AML patients (HR=1.93, 95% CI 1.44 to 2.42). KMT2A -PTD indicated no prognostic impact on EFS in total population (HR=1.26, 95% CI 0.86 to 1.66). However, in the sensitivity analysis, KMT2A -PTD resulted in poor EFS (HR=1.34, 95% CI 1.04 to 1.64) when deleting the study with a relatively obvious effect on the combined HR. In the subgroup analysis, KMT2A -PTD was associated with poor EFS in old AML patients (HR=1.64, 95% CI 1.25 to 2.03). Conclusion: The findings indicated that KMT2A -PTD had an adverse impact on the prognosis of patients with AML in the total population, and the conclusion can also be applied to some subgroups including karyotypically normal AML and old AML patients. KMT2A -PTD may be a promising genetic biomarker in patients with AML in the future. Trial registration number: CRD42021227185.